Estudo do comportamento hidrodinâmico de um reator anaeróbio-aeróbio de leito fixo tratando efluente bovino - Nascimento Junior, Sérgio Luiz (2013)
This study aimed to evaluate the hydrodynamic behavior of an anaerobic-aerobic fixed bed (RAALF), operating in three hydraulic retention times (HRT) - 22h, 16h, and 10h. The reactor consists of a 100 mm diameter PVC pipe and 1.2m high, with a volume of 4.3 L, operated in upflow, with power held by peristaltic pump and used as substrate raw wastewater from slaughter cattle. For immobilization of biomass, two materials was used: Luffa cilyndrica (vegetable cellulose) in the anaerobic phase and polyurethane foam in aerobic phase. The hydrodynamic profiles consisted of testing stimulus-response type pulse, using bromophenol blue as a tracer. Analyses of physico-chemical parameters were made in order to determine the apparent steady state of the RAALF. The results of this monitoring indicate high levels of organic matter removal in terms of COD, averaging 93.3% for COD gross and 90.5% for filtered COD. The removal of suspended solids also achieved good percentage average of 97.7%. Decay was observed over the concentration of tracer demonstrated by actual TDHS greater than the theoretical. This phenomenon can be attributed to adsorption of the tracer through support. There was an advance peak concentration in all assays, which can be explained by the possible presence of preferential paths. The correlations of the models dispersion (R2) indicate a closer approximation of the model of complete mixing tanks in series (N-CSTR) with an average of three reactors in series pertaining to the profiles HDT of 22h and 16h and two reactors in series the HRT of 10h. The results of the study were not identified hydrodynamic deviations ideality as dead zones and short-circuit hydraulic. As the hydraulic efficiency for all tests, the data for this parameter was found higher than 0.75, indicating good hydraulic efficiency.